NUMERICAL SIMULATION OF SETTLEMENT BEHAVIOUR OF AXIALLY LOADED PILES USED FOR HIGH-RISE BUILDING. - Gowthaman, S.; Nasvi, M.C.M.; Krishnya, S. (7th International Conference on Sustainable Built Environment, University of Peradeniya, Sri Lanka, 2016)
The reliable prediction settlement of pile foundation at typical working load remains one of the major geotechnical engineering problems. In this research, settlement behaviour of a pile foundation located in sandy-silt, under the loads from high-rised building is simulated in 2D using a finite element program (PLAXIS). Three different types of analysis were investigated: a linear elastic (LE) analysis where the soil was assumed as linear-elastic material, a simple nonlinear analysis where the soil was completely assumed as Mohrcoulomb (MC) model and an advanced nonlinear analysis where the soil was completely assumed as Hardening-Soil (HS) model. A comparison was done between the predicted settlement from Finite element analysis and field settlement values. Based on the results of analysis, it is suggested that although complete MC model shows good agreement with the settlement behaviour obtained from field static load test at lower working loads, MC model is not adequate to capture the settlement prediction at higher working loads. In addition, modelling the soil completely using HS model is required to capture the safe settlement prediction at higher working loads. Finally, this scenario can be applied for the similar problems in settlement prediction using numerical methods.
Keywords: Hardening-soil model; Linear-elastic; Mohr-coulomb model; Settlement; axially loaded piles